Peningkatan Hasil Belajar Siswa Dengan Menggunakan Metode Berdiferensiasi Pada Mata Pelajaran PAI VII.4 UPTD SMP Negeri 2 Kec. Harau - Nur Arifah; Syawaluddin Syawaluddin; Deslita Deslita; Selvi Yanti; Azimatul Husna; Nurhasanah Nurhasanah (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low learning outcomes of students in Islamic Religious Education at VII.4 UPTD SMP Negeri 2 Kec. Harau. Differentiated learning is learning that is most appropriate and accurate in conveying messages and will really help students' understanding. The aim of this research is to: determine the improvement in students' Islamic Religious Education (PAI) learning outcomes through differentiated methods at VII.4 UPTD SMP Negeri 2 Kec. Harau. The data collection techniques used were tests and observations. The results of the research show that the differentiation method in PAI subjects is able to increase students' learning motivation, especially students in class VII.4 UPTD SMP Negeri 2 Kec. Harau. Quantitative evidence can be seen of an increase in the motivation variable test from the first and second meetings. The test results also experienced an increase from the pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. Meanwhile, qualitative evidence can be explained from the number of students who stated that they were happy with the use of video media, the growth of students' motivation and concentration on PAI subjects.